Nivel de rentabilidad de las ventas del departamento de televentas del Almacén Baratodo del Grupo Unicomer S.A. del año 2017-2018. - Reinoso Hernández, María Victoria (2020)
The Telesales Department of the Baratoho Warehouse in the city of Babahoyo created in August 2016 dedicated to sales by telephone calls through a Bright Pattern base where the repetitive customers are recorded; It will be the place where this case study will be carried out, a study of the level of profitability of sales will be carried out in the years 2017 - 2018 of the warehouse, where in 2017 it had a decrease compared to the year 2018. The objective is to know the level of profitability of the sales of the Telesales Department of the Baratodo Warehouse of the Unicomer Group in 2018 has obtained a decrease for different reasons such as the counter-delivery policy, the lower number of repetitive customers, advertising, the number of workers among others. The method used was observation and interview with the supervisor to learn more about the decrease of 15.98% between the year 2017-2018.